Perfil de egressos do Programa de Pós-Graduação Interdisciplinar em Estudos do Lazer (PPGIEL) da UFMG: um estudo da trajetória profissional e do mercado de trabalho - Renan Monticeli Furtado (2021)
Introduction - Graduates of training courses can provide information relevant to the educational institutions that trained them. By conducting research with graduates, it is possible to gain knowledge about the professional trajectory of former students, raise upto-date socio-demographic data on the community, in addition to allowing the evaluation of the effectiveness of the training processes offered. The Interdisciplinary Postgraduate Program in Leisure Studies at the Federal University of Minas Gerais (PPGIEL-UFMG) did not have scientific research investigating the graduates of the program. Objectives - This research aimed to analyze the professional profile of graduates of the master's and doctoral courses at PPGIEL-UFMG. In addition, to identify aspects related to the professional performance of this sample of graduates, investigating the insertion of graduates in the fields of professional activity, considering issues such as monthly income, working hours and employment relationship after completing postgraduate studies. Methods - Designed as exploratory-descriptive research with a mixed approach, the study used as a data collection instrument a semi-structured questionnaire applied with masters and doctors graduated from PPGIEL in the period from 2008 to 2020. Altogether, 120 graduates participated as respondents of the research. This sample is formed by 76 graduates of the master's course; 28 graduates of the doctoral course; and 16 graduates who completed both courses. In view of this, the total sample of graduates who answered the survey questionnaire corresponds to 54% of graduates from the Leisure Studies program. Results - The survey results contribute to understanding the academic and professional profile of the program's graduates. The study found that most of the PPGIEL graduates are professionally inserted in the training area offered by the master's and doctoral courses in Leisure Studies. However, there are differences in the professional trajectories of graduates according to the level of education. In general, masters are inserted in diversified fields of activity, in the educational context and beyond, and doctors have a more homogeneous professional trajectory, centered on an academic career. Conclusions - Although there are different professional trajectories among the researched groups, with the data obtained it was possible to conclude that the PPGIEL has fulfilled its objective of inserting professionals, predominantly, in the context of teaching in higher education.